2022
DOI: 10.1017/s135561772200042x
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised high-frequency smartphone-based cognitive assessments are reliable, valid, and feasible in older adults at risk for Alzheimer’s disease

Abstract: Objective: Smartphones have the potential for capturing subtle changes in cognition that characterize preclinical Alzheimer’s disease (AD) in older adults. The Ambulatory Research in Cognition (ARC) smartphone application is based on principles from ecological momentary assessment (EMA) and administers brief tests of associative memory, processing speed, and working memory up to 4 times per day over 7 consecutive days. ARC was designed to be administered unsupervised using participants’ personal devices i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 57 publications
(86 reference statements)
7
45
0
Order By: Relevance
“…However, our study did not use a composite measure but individual memory scores. As expected, they were most strongly associated with conventional memory measures (r = 0.27-0.40), which align nicely with relationships of pure memory measures in the abovementioned studies (r = 0.30-0.47 and −0.22-0.32) (15,19). Thus, our results support the notion that the mobile app-based memory measures assess relevant cognitive functions as confirmed by conventional cognitive outcomes but also showed associations with speed and executive function.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, our study did not use a composite measure but individual memory scores. As expected, they were most strongly associated with conventional memory measures (r = 0.27-0.40), which align nicely with relationships of pure memory measures in the abovementioned studies (r = 0.30-0.47 and −0.22-0.32) (15,19). Thus, our results support the notion that the mobile app-based memory measures assess relevant cognitive functions as confirmed by conventional cognitive outcomes but also showed associations with speed and executive function.…”
Section: Discussionsupporting
confidence: 87%
“…Another recent study ( 34 ) used a composite of similar but not identical tasks as used in this study and demonstrated a strong correlation to PACC ( r = 0.51) in cognitively normal individuals without cognitive complaints. A study using the Ambulatory Research in Cognition app ( 15 ) in primarily cognitively normal participants (again using a composite of cognitive measures) reported a strong correlation with a global composite similar to the PACC ( r = −0.53). Our study found that our mobile app-based tasks were significantly associated with the PACC5 ( r = 0.3–0.5), with similar effect sizes reported in previous work ( 15 , 19 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations